The Effects of Sign Language on Hearing EFL Students’ Vocabulary Memorization - Isfina Zannuba Arifah (Journal on Education, 2024)
Acquiring vocabulary is fundamental to mastering the four linguistic skills: listening, speaking, reading, and writing. Various methods exist for teaching vocabulary, one of which involves the use of gestures. Numerous previous studies underscore the significance of incorporating gestures in vocabulary instruction. Similarly, some studies have explored the use of sign language in classroom settings, as sign language employs gestures to convey the speaker's (signer's) meaning. However, research on this topic is rarely conducted in Indonesia. Consequently, the researcher undertook a similar study in Indonesia, involving 25 hearing EFL Indonesian learners who were randomly assigned to either an experimental or a control group. The vocabulary was delivered using two short stories containing the targeted vocabulary words. Following four treatment sessions, a vocabulary test was administered. The results indicated no significant difference between the mean scores of the experimental group and the control group. This finding contradicts previous research that has demonstrated a significant difference in vocabulary acquisition between students who use sign language and those who do not. Future research could explore the effects of sign language on different subjects or with alternative methodologies to determine whether similar or different results will be obtained.